Necrosis of the Glabella After Injection With Hyaluronic Acid Into the Forehead. Issue 7 (October 2018) - Han, Jingjian; He, Yanzi; Liu, Kuikui; Yang, Qinghua
Abstract : Abstract: Skin necrosis is a rare but severe potential complication after injection of hyaluronic acid (HA). Based on the understanding of the causes and mechanisms of this complication, many precautions have been proposed. Still, this adverse reaction happened from time to time. Here, the authors present a patient with glabellar skin necrosis following an injection into the forehead using HA filler. Although not uncommon, this patient might suggest an alternative cause or mechanism of tissue necrosis following HA injection besides intravascular injection or extravascular compression directly by HA filler. Further study is needed to examine other possible causes in order to eliminate this risk.